2005
DOI: 10.2113/11.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Vulnerability of a Municipal Well Field to Contamination in a Karst Aquifer

Abstract: Proposed expansion of extractive lime-rock mines near the Miami-Dade County Northwest well field and Everglades wetland areas has garnered intense scrutiny by government, public, environmental stakeholders, and the media because of concern that mining will increase the risk of pathogen contamination. Rock mines are excavated to the same depth as the well field's primary producing zone. The underlying karst Biscayne aquifer is a triple-porosity system characterized by (1) a matrix of interparticle porosity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Following such an approach is particularly useful since properties of many tracers and their interactions with the environment cannot always be inferred from the literature. However, the authors are aware of only one study where microsphere tracer employed to karst groundwater is compared to the response of a real microorganism in laboratory tests (Renken et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following such an approach is particularly useful since properties of many tracers and their interactions with the environment cannot always be inferred from the literature. However, the authors are aware of only one study where microsphere tracer employed to karst groundwater is compared to the response of a real microorganism in laboratory tests (Renken et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have identified the benefits of employing particulate tracers instead of solutes for assessing the risk of particulate contamination impacting groundwater quality in a range of hydrogeological environments (including karst), where fluorescent microspheres have been widely used as surrogates for bacteria (Harvey et al 1989;Harvey and Harms 2002;Auckenthaler et al 2002) and protozoa (Renken et al 2005) of comparable size. However, although particle size is frequently the dominant criterion considered in microsphere selection, conclusive evidence of their suitability has rarely been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Renken et al (2005) used tracers to calibrate models used in south Florida by regulatory agencies to evaluate the impacts of groundwater flow and potential contamination of municipal supply wells from additional mining proposed in the vicinity of those supply wells. Tracers used in that calibration even revealed groundwater flow occurring in the vicinity of these mine pits that was orders of magnitude greater than predicted by the models developed by the regulatory agencies.…”
Section: Evaluation Alternativesmentioning
confidence: 99%
“…In order to understand such processes, the 2D cross-sectional potable aquifer model was designed as shown in Figure 3. The potable aquifer was assumed to be relatively deep (300 m with a reducing condition), where the municipal or high-capacity wells produced a large amount of groundwater, which was then distributed for residential purposes [48,49]. In addition, the width and thickness of the potable aquifer were assigned as 200 m and 40 m, respectively, with the size of grid blocks of 2 m; the total number of grid blocks was 2,000 (100 × 20).…”
Section: Model Descriptionmentioning
confidence: 99%